Multi-Locus Sequence Typing of Bartonella bacilliformis DNA Performed Directly from Blood of Patients with Oroya's Fever During a Peruvian Outbreak. - Pons, Maria J (2016)
Background Bartonella bacilliformis is the etiological agent of Carrion’s disease, a neglected tropical poverty-linked illness. This infection is endemic of Andean regions and it is estimated that approximately 1.7 million of South Americans are at risk. This bacterium is a fastidious slow growing microorganism, which is difficult and cumbersome to isolate from clinical sources, thereby hindering the availability of phylogenetic relationship of clinical samples. The aim of this study was to perform Multi Locus Sequence Typing of B. bacilliformis directly in blood from patients diagnosed with Oroya fever during an outbreak in Northern Peru. Methodology/Principal Findings DNA extracted among blood samples from patients diagnosed with Oroya’s fever were analyzed with MLST, with the amplification of 7 genetic loci (ftsZ, flaA, ribC, rnpB, rpoB, bvrR and groEL) and a phylogenetic analysis of the different Sequence Types (ST) was performed. A total of 4 different ST were identified. The most frequently found was ST1 present in 66% of samples. Additionally, two samples presented a new allelic profile, belonging to new STs (ST 9 and ST 10), which were closely related to ST1. Conclusions/Significance The present data demonstrate that B. bacilliformis MLST studies may be possible directly from blood samples, being a promising approach for epidemiological studies. During the outbreak the STs of B. bacilliformis were found to be heterogeneous, albeit closely related, probably reflecting the evolution from a common ancestor colonizing the area. Additional studies including new samples and areas are needed, in order to obtain better knowledge of phylogenetic scenario B. bacilliformis